2008
DOI: 10.1037/0893-164x.22.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of heavy drinking and drinking problems over the first 4 years of marriage.

Abstract: This study investigated the factors predictive of heavy drinking and drinking problems over the early years of marriage, focusing on the premarital drinking and relatively stable individual risk and protective factors that were present prior to marriage, and on social-interpersonal factors that may change or emerge over marriage. Newlywed couples were assessed at the time of marriage, and at the 1 st , 2 nd , and 4 th anniversaries with respect to frequency of heavy drinking and the extent of drinking problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
81
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 70 publications
14
81
3
Order By: Relevance
“…Of those people who continue to drink heavily after the transition, there is a tendency for married partners to be concordant in terms of their heavy drinking (Labouvie, 1996;Leonard and Homish, 2008). This effect is not entirely surprising.…”
Section: Concordant and Discrepant Heavy Drinkingmentioning
confidence: 81%
“…Of those people who continue to drink heavily after the transition, there is a tendency for married partners to be concordant in terms of their heavy drinking (Labouvie, 1996;Leonard and Homish, 2008). This effect is not entirely surprising.…”
Section: Concordant and Discrepant Heavy Drinkingmentioning
confidence: 81%
“…The focus of the current study is on a subset of the social network (i.e., drinking buddies) that has been shown to be predictive of both heavy drinking and alcohol problems in both men and women (Leonard and Homish, 2008). Given this relationship, it is reasonable to consider factors that are specifi c to alcohol use as possible predictors of changes in the composition of the social network as it relates to alcohol use.…”
Section: Factors Related To Changes In Social Networkmentioning
confidence: 99%
“…In the midst of these reductions and reorganization of the social network, its infl uence may be substantially reduced. To determine if peer infl uence were prominent after the transition to marriage, Leonard and Homish (2008) examined the social network of newly married couples during the fi rst 4 years of marriage to determine if the number of drinking buddies were longitudinally predictive of heavy drinking and alcohol problems in men and women after controlling for a variety of individual, relationship, and sociodemographic factors. To allow for changes in the social network membership over time, the number of drinking buddies was modeled as a time-varying predictor.…”
Section: A Variety Of Factors Influence Changesmentioning
confidence: 99%
“…Studies have shown that individuals with antisociality/generalized violence traits are prone to SUD problems (HoltzworthMunroe et al, 2000;Leonard and Homish, 2008;Walsh et al, 2010). This may be because those with higher levels of antisociality/generalized violence are more likely to engage in a broad range of socially deviant behaviors, including heavy drinking and other drug use.…”
mentioning
confidence: 98%